El Gato Ensombrerado - Seuss, Dr. Dr.; Lazaro Leon, Georgina; Mlawer, Teresa (New York : Random House, 2015)
A zany but well-meaning cat brings a cheerful, exotic, and exuberant form of chaos to a household of two young children one rainy day while their mother is out.
Keywords: Cat in the Hat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Orderliness -- Juvenile fiction; Cleanliness -- Juvenile fiction; Cat in the Hat (Fictitious character) -- Fiction; Cats -- Fiction; Orderliness -- Fiction; Cleanliness -- Fiction; Spanish language materials; Gatos -- Novela juvenil; Sentido de orden -- Novela juvenil; Limpieza -- Novela juvenil; Stories in rhyme